Understanding of Contract Fundamentals for Tourism Awareness Groups in Kare Village, Madiun Regency - Lintang Yudhantaka; Miko Aditya Suharto; Much. Arief Syahroni (VSJ | Veteran Society : Jurnal Pengabdian Masyarakat, 2021)
Madiun Regency is not only rich in natural resources but also rich in human resources. Until now, there is a lot of business potential in Madiun Regency, and to create a good business climate, good facilities and infrastructure are needed as well. For this reason, strategies and policies, and implementation programs are needed to create good tourism and the importance of synergy between tourism actors. For this reason, the urgency of understanding contracts concerning business development is very much needed in the development and management of Micro, Small, and Medium Enterprises (MSMEs) in Madiun. The contract is intended as a forum for partnership in the development and management of business activities. Understanding contracts in business activities is essential because the existence of a contract can provide a reference or guideline for the parties in carrying out their business activities. In addition, the existence of a contract will undoubtedly provide more legal certainty for the parties. It can reduce the potential for disputes to occur because the distribution of rights and obligations has been regulated based on the parties' agreement.